Stress and quality of life among susceptible Thai people during COVID-19 pandemic - Chotklang, Duangruedee; Padphai, Isaree; Porusia, Mitoriana; Chotchai, Tepthai; Ekathat, Thitikan (Intelektual Pustaka Media Utama, 2023)
People with underlying disease (diabetes mellitus, and hypertension) could be stressed during COVID-19 pandemic. This study was investigated stress levels and quality of life among diabetes mellitus and/or hypertension patients, and factors related to quality of life in Khon Kaen during COVID-19 pandemic. This cross-sectional analytical study was conducted 270 samples. Multilevel logistic regression was performed to identify the influence of stress level and quality of life (QoL). The results showed that most of the samples had a moderate level of stress (78.5%), and a high level of stress (3.3%). For overall QoL, it was found that most of them had moderate level (77.8%), and poor level (7.8%). The likelihood of poor QOL was 5.5 times (adj. OR=5.5; 95% CI: 1.6 to 18.1) of income decreasing due to economic downturn, no impact to moderate impact and not COVID-19 immunized had 3.4 times the likelihood of poor QOL (adj. OR=3.4; 95% CI:1.2 to 9.2) with statistical significance at 0.05 level. It could be concluded that nearly 2.5–3 times, samples had a poor to moderate quality of life, due to stress and economic issues that affected people's quality of life during the COVID-19 pandemic.